PENERAPAN METODE EDUTAINMENT UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN TEMATIK SEKOLAH DASAR - Suhada, Suhada; Sabri, Tahmid; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractCan the Edutainment method improve students' learning outcomes in Thematic Class 1 lesson of North Pontianak 2nd Elementary School. The research method used in this research is descriptive method with form of collaborative class action research. Research subjects of students and teachers of class I with the number of students 27. This research is done III cycle and each cycle consists of 1 meeting. The results obtained are the ability of teachers to plan learning by using Edutainment method with the total score in the first cycle is 14.40 or 2.88 average. In cycle II the total score increased to 15.67 or 3.13 in average. In cycle III the total score increased to 16.00 or 3.20 average. The results obtained by the ability of teachers in implementing learning by using Edutainment method with a total cycle score I 13.21 or 3.30 average. In cycle II the total score 14.46 or 3.61 average. In total cycle III 15.08 or 3.77 average. In this study the student learning outcomes also increased with student learning outcomes, the first cycle of 86.30, the second cycle of 89.26, and the third cycle of 90.00. From the data obtained shows that the use of Edutainment method can improve the ability of teachers in planning, melaksanakandan student learning outcomes in class ICT learningKeywords: Metode Edutainment, Pembelajaran Tematik